Representasi Citra Victoria’s Secret di Forbes.com terkait Kasus Body Shaming - Rizkiana, Marcella; Natalia, El Chris (Jurnal InterAct, 2021)
Victoria Secret's (VS) is one of the companies that experienced a crisis due to the body shaming case carried out by chief marketing officer in the company. The media can frame information about the company by focusing on its strengths or weaknesses in its reporting. Forbes.com is an online business media that participates in reporting on the body shaming case faced by VS. The purpose of this study is to determine the representation of the Victoria's Secret (VS) corporate image in Forbes.com related to the body shaming case. The research method used is a qualitative method with analysis of the framing model of Robert Entman. This study analyzes the news on Forbes.com regarding VS in November 2018. The results of this study indicate that the representation of the Victoria's Secret company image is negatively published in the news on Forbes.com because of the crisis experienced. The case of body shaming is not handled properly so that it cannot be controlled or detained which results in losses for the company.